Analysis of Mexico's agribusiness sector 2020-2021 (Revista de Investigaciones Universidad del Quindío, 2022)
Agriculture has prevailed over thousands of years, thanks to it a great diversity of products is obtained, which meet the demands of society, but for this it has needed various factors, to be able to transform this type of materials into products, which is done through industrialization, whose task is to process this raw material obtained through agriculture to transform it into a product and with this adding value, with which it will generate resources for both parties, the union of this type of activities is known as agribusiness. This work will be done through a small analysis of the agro-industrial sector in Mexico in a comparison of the years 2020 and 2021, with the aim of describing the changes that have arisen in these years, through a descriptive and exploratory methodology.
Keywords: agriculture; agribusiness; demand; industry; society